EL GENERO LOTAGNOSTUS (TRILOBITA, AGNOSTIDA) EN LA FORMACION SANTA ROSITA (JUJUY, ARGENTINA) Y SU SIGNIFICADO CRONOLOGICO (Ameghiniana, 2013)
The genus Lotagnostus found for the first time in the Cambrian-Ordovician Basin of northwest Argentina is described. This Upper Cambrian genus is found in the lower levels of the Santa Rosita Fonnation. The outcrops are located near Huacalera (Jujuy, Argentina). The age of Parabolina (Neoparabolina] frequens is also discussed.